2014
DOI: 10.1371/journal.pone.0097315
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Releasing Aspirin, ACS14, Attenuates High Glucose-Induced Increased Methylglyoxal and Oxidative Stress in Cultured Vascular Smooth Muscle Cells

Abstract: Hydrogen sulfide is a gasotransmitter with vasodilatory and anti-inflammatory properties. Aspirin is an irreversible cyclooxygenase inhibitor anti-inflammatory drug. ACS14 is a novel synthetic hydrogen sulfide releasing aspirin which inhibits cyclooxygenase and has antioxidant effects. Methylglyoxal is a chemically active metabolite of glucose and fructose, and a major precursor of advanced glycation end products formation. Methylglyoxal is harmful when produced in excess. Plasma methylglyoxal levels are signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…However, Huang et al found that treatment with NaHS or H 2 S releasing donor, ACS14, for 24 h attenuated the increase in iNOS expression caused by high glucose (25 mM). This is similar to the inhibitory effect of H 2 S on iNOS expression in heart [ 134 ]. These data suggest that H 2 S may regulate iNOS expression in a time-dependent manner.…”
Section: H 2 S-no Interaction In Cardiovascsupporting
confidence: 80%
See 1 more Smart Citation
“…However, Huang et al found that treatment with NaHS or H 2 S releasing donor, ACS14, for 24 h attenuated the increase in iNOS expression caused by high glucose (25 mM). This is similar to the inhibitory effect of H 2 S on iNOS expression in heart [ 134 ]. These data suggest that H 2 S may regulate iNOS expression in a time-dependent manner.…”
Section: H 2 S-no Interaction In Cardiovascsupporting
confidence: 80%
“…They are accompanied by oxidative stress, which is the result of imbalance between ROS generating and ROS-scavenging systems [ 145 147 ]. It is now a well-established fact that ROS generation is ramped up in heart [ 134 ] and blood vessels [ 135 ] during cardiovascular pathologies. Oxidative stress is a result of excessive production of ROS like O 2 − , • HO, H 2 O 2 , NO, ONOO − , and HClO, mainly as a byproducts of cellular aerobic metabolism.…”
Section: Role Of H 2 S-no Interaction In Oxmentioning
confidence: 99%
“…MGO increases arginase expression in endothelial cells and vascular smooth muscle cells (VSMCs) (141). ROS promote the pathological elevation of arginase; however, whether MGO-induced oxidative stress in endothelial cells and VSMCs (103,245,609,610) is involved in the MGO-induced increased expression of arginase remains to be determined. In VSMCs, MGO also decreases hydrogen sulfide levels (102).…”
Section: A Methylglyoxal and Endothelial Dysfunction In Diabetesmentioning
confidence: 99%
“…This compound has gastric H 2 S Donors and H 2 S Biosynthesis Inhibitors mucosa sparing properties (Sparatore et al, 2009) as well as antihypertensive, vascular protective effects, and protective effects against myocardial ischemiareperfusion in rodent models (Rossoni et al, 2010). ACS14 also protects microglial cells from amyloidb-peptide-induced cytotoxicity (Liu et al, 2011b), protects endothelial cells against methylglyoxal-induced dysfunction (Huang et al, 2014), and inhibits platelet aggregation and exerts antithrombotic effects in vitro and in vivo (Pircher et al, 2012;Gao et al, 2015). One of the problems with the available literature with ACS14 is that head-to-head comparisons with aspirin are sometimes missing (e.g., Giustarini et al, 2010) or sometimes the comparisons are difficult to evaluate.…”
Section: Combined (Or Hybrid) Molecules: H 2 S-donating Derivamentioning
confidence: 99%